1999
DOI: 10.1016/s0014-5793(99)00871-6
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PPARγ inhibits cell growth and induces apoptosis in human gastric cancer cells

Abstract: We investigated the expression of peroxisome proliferator-activated receptor Q Q (PPARQ Q) and the role of PPARQ Q in cell growth in human gastric cancer cells. Reverse transcriptionpolymerase chain reaction, Northern blot and Western blot analyses showed that a human gastric cancer cell line, MKN45, expressed PPARQ Q mRNA and protein. Luciferase assay in MKN45 cells showed that troglitazone, a selective ligand for PPARQ Q, transactivated the transcription of a peroxisome proliferator response element-driven p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
147
2
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(162 citation statements)
references
References 25 publications
12
147
2
1
Order By: Relevance
“…In vitro studies have shown that activation of the PPARg signaling pathway by ligands inhibits growth and induces differentiation and apoptosis in cultured cells of leukemia (Asou et al, 1999), bladder cancer (Guan et al, 1999), choriocarcinoma (Keelan et al, 1999), prostate cancer (Kubota et al, 1998), pancreatic carcinoma (Motomura et al, 2000), chondrosarcoma (Nishida et al, 2002), colon cancer (Sarraf et al, 1998), gastric cancer (Takahashi et al, 1999) and lung cancer (Tsubouchi et al, 2000). As the discovery of the PAX8-PPARg fusion gene in human follicular thyroid carcinoma and the demonstration of loss of PPARg transcription activity in the PAX8-PPARg fusion gene , there has been great interest in understanding the role of PPARg in the development and progression of follicular thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that activation of the PPARg signaling pathway by ligands inhibits growth and induces differentiation and apoptosis in cultured cells of leukemia (Asou et al, 1999), bladder cancer (Guan et al, 1999), choriocarcinoma (Keelan et al, 1999), prostate cancer (Kubota et al, 1998), pancreatic carcinoma (Motomura et al, 2000), chondrosarcoma (Nishida et al, 2002), colon cancer (Sarraf et al, 1998), gastric cancer (Takahashi et al, 1999) and lung cancer (Tsubouchi et al, 2000). As the discovery of the PAX8-PPARg fusion gene in human follicular thyroid carcinoma and the demonstration of loss of PPARg transcription activity in the PAX8-PPARg fusion gene , there has been great interest in understanding the role of PPARg in the development and progression of follicular thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…For reverse transcriptase-polymerase chain reaction (RT -PCR), RNA samples (5 mg) were reverse-transcribed to cDNA using reverse transcriptase (ReverTra Ace, Toyobo Co. Ltd., Osaka, Japan) and subsequently amplified by PCR using as a sense primer, 5'-TCTCTCCGTAATGGAAGACC-3' and an antisense primer, 5'-GCATTATGAGAC-ATCCCCAC-3' as previously reported (Takahashi et al, 1999). Human adult normal adipose total RNA was purchased from BioChain Institute, Inc, CA, USA (Catalogue Number 061005).…”
Section: Rna Extraction and Rt -Pcrmentioning
confidence: 99%
“…Recent studies reported that 15-deoxy-D 12,14 -prostaglandin J 2 (15d-PGJ 2 ), the most potent endogenous ligand for PPARg, and the synthetic PPARg ligand thiazolidinedione (TZD) can induce terminal differentiation and growth inhibition of human liposarcoma (Tontonoz et al, 1997), breast (Elstner et al, 1998;Yee et al, 1999), prostate (Kubota et al, 1998), colon (Sarraf et al, 1998;Kitamura et al, 1999), gastric (Takahashi et al, 1999;Sato et al, 2000), lung (Chang and Szabo, 2000;Tsubouchi et al, 2000), and pancreas (Motomura et al, 2000;Elnemr et al, 2000) cancer cells, as well as hepatoma cells (Koga et al, 2001) in vitro and in vivo. The in vivo induction of histological and biochemical differentiation of liposarcomas by clinical trial of troglitazone administration was reported by Demetri et al (1999).…”
mentioning
confidence: 99%
“…Several studies have shown that TZDs can lead to growth inhibition in liposarcoma, 12 breast cancer, 13,14 colon cancer, [15][16][17] prostatic cancer 18 and gastric cancer. 19 In the present study, we observed the expression of PPAR␥ and investigated the effects of TZD and their mechanism on pancreatic cancers.Pancreatic carcinoma is one of the most malignant cancers. At the time of diagnosis, over 80% of the patients have advanced regional disease or distant metastasis.…”
mentioning
confidence: 94%